Visionary women : how Rachel Carson, Jane Jacobs, Jane Goodall, and Alice Waters changed our world - Barnet, Andrea (Ecco, an imprint of HarperCollinsPublishers, 2018)
Discusses four influential women linked by their choice to break with convention, exploring how their work in their respective fields helped to ignite the progressive movement and offered a more positive way to think about the world.